Pedro Vásquez Ruesta, un forestal comprometido con el manejo de la fauna silvestre en el Perú - Tovar Narváez, Antonio (2024)
Pedro Vásquez Ruesta (1954-2023) was an outstanding Peruvian forestry engineer and professor at the Faculty of Forestry Sciences of the Universidad Nacional Agraria La Molina (UNALM), who dedicated his life to university teaching and scientific research between 1978 and 2023. Pedro Vásquez published many books and scientific articles on wildlife management and natural protected areas in Peru, especially on the white-tailed deer and its management through sport hunting in the El Angolo Hunting Reserve (Piura), the behavior of caimans and the feeding ecology of sea lions on southern Peru, and the sustainable management of several natural protected areas. He received awards and recognition for his outstanding work for the benefit of nature conservation, even a species of frog was named after him (Osteocephalus vasquezi). But above all, he received the affection and admiration of his family, friends and students. The purpose of this article is to pay tribute to Pedro Vasquez, remembering his life and academic legacy.